PHYSIOLOGIC PATTERNS OF SLEEP ON EEG, MASKING OF EPILEPTIFORM ACTIVITY - L. Yu. Glukhova; K. Yu. Mukhin; E. I. Barletova; M. A. Nikitina; A. M. Sobornova; G. V. Kuzmitch (Русский журнал детской неврологии, 2015)
Physiologic patterns of sleep on EEG can sometimes be similar to epileptiform activity and even to the EEG pattern of epileptic seizures, but they have no connection to epilepsy and their incorrect interpretation may lead to overdiagnosis of epilepsy. These sleep patterns include vertex transients, K-complexes, hypnagogic hypersynchrony, 14 and 6 Hz positive bursts, wicket-potentials, etc. The main distinctive features of acute physiological phenomena of sleep unlike epileptiform activity are stereotyped, monomorphic morphology of waves, which frequently has rhythmic, arcuate pattern, often with change of lateralization, mainly dominated in the first stages of sleep (N1-N2), with their reduction in the deeper stages and transition to delta sleep (N3). The correct interpretation of physiological sharp-wave phenomena of sleep on EEG requires considerable training and experience of the physician. Our review includes a variety of physiological sleep patterns, which can mimic epileptiform activity on EEG, their criteria of diagnostic with demonstration of own illustrations of EEG.